2022
DOI: 10.3389/fphys.2021.752455
|View full text |Cite
|
Sign up to set email alerts
|

In Hamstring Muscles of Patients With Knee Osteoarthritis an Increased Ultrasound Shear Modulus Indicates a Permanently Elevated Muscle Tonus

Abstract: BackgroundSome patients with knee osteoarthritis (KOA) show pain, stiffness and limited flexion and extension at the back of the knee, leading to dysfunction and affecting life. This may be related to changes in the biomechanical properties of skeletal muscles. Shear wave elastography (SWE) can detect these changes by measuring muscle shear modulus.AimsTo investigate hamstring muscle shear modulus of healthy people and patients was studied using SWE method, and the correlation analysis between the Western Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The exclusion of muscle fascia from the measurement box was clearly stated in eight articles (26.6%) (Aljinović et al, 2020;Friede et al, 2020;Gökşen et al, 2021;Klauser et al, 2022;Koppenhaver et al, 2020;Murillo et al, 2019;Takashima et al, 2017;Zhang et al, 2022). The example images of eight more studies (26.6%) suggest the avoidance of fascia in the measurements (Botanlioglu et al, 2013;Botanlıoğlu et al, 2019;Ertekin et al, 2021;Leong et al, 2016;Li et al, 2021;Lin et al, 2022;Sedlackova et al, 2021;Taş et al, 2018) (Figure S1).…”
Section: Critical Appraisal Of Swe Methods (Supplementary Items)mentioning
confidence: 98%
“…The exclusion of muscle fascia from the measurement box was clearly stated in eight articles (26.6%) (Aljinović et al, 2020;Friede et al, 2020;Gökşen et al, 2021;Klauser et al, 2022;Koppenhaver et al, 2020;Murillo et al, 2019;Takashima et al, 2017;Zhang et al, 2022). The example images of eight more studies (26.6%) suggest the avoidance of fascia in the measurements (Botanlioglu et al, 2013;Botanlıoğlu et al, 2019;Ertekin et al, 2021;Leong et al, 2016;Li et al, 2021;Lin et al, 2022;Sedlackova et al, 2021;Taş et al, 2018) (Figure S1).…”
Section: Critical Appraisal Of Swe Methods (Supplementary Items)mentioning
confidence: 98%
“…81 These studies showed differences of SWE values in the aforementioned anatomical structures between OA and non-OA patients, [78][79][80][81] as well as correlation with knee pain and physical function. 81 Contrast-enhanced ultrasound provides the evaluation of dynamic blood perfusion via signals from a gas-filled microbubble contrast agent. 82 A prospective study included 31 patients with different degrees of radiographic knee OA.…”
Section: Advanced Ultrasound Imaging -Shear Wave Elastography Contras...mentioning
confidence: 96%
“… 77 SWE has been applied to evaluate femoral cartilage in OA-affected knees, 78 abductor pollicis brevis and flexor pollicis brevis muscles in patients with thumb carpometacarpal OA, 79 vastus lateralis muscle in painful knee OA patients, 80 and in hamstring muscles of knee OA patients. 81 These studies showed differences of SWE values in the aforementioned anatomical structures between OA and non-OA patients, 78 81 as well as correlation with knee pain and physical function. 81 …”
Section: Spectral and Photon-counting Ct In Oa Imagingmentioning
confidence: 97%
See 1 more Smart Citation
“…At the knee, the most well studied joint, multiple authors have indeed observed muscle strength deficits, problems in voluntary muscle activation, muscle mass or volume declines/deficits, deficits in muscle flexibility, excessive muscle tone, generalized muscle weakness of the affected limb, muscle endurance losses, muscle power and force control ability [21][22][23][24][25][26][27][28]. Along with associated alterations in neuromuscular communication processes one or more of these attributes may be instrumental in inducing various molecular and cellular adaptations within both muscle as well as cartilage tissues that further provoke pathological joint changes [29], while altering dynamic joint stability that appears to impact osteoarthritis progression [28].…”
Section: As Ofmentioning
confidence: 99%